Interdependence in social and territorial planning theories and sustainable development principles - Giuliana Quattrone; Afio Zannou (European Regional Science Association (ERSA), 1998)
This paper intends to deal with interdependence relationships between social and planning theories and their environment principles in a context of a sustainable development. Within any community, people through their activities interact with the physical environment, giving to each region its characteristics and specificity. Then, the management of the activities and the environment needs regulations because the socially unsatisfactory outcomes of the development process give rise to the need of intervention of government. This intervention is enabled through the objectives and the implementation of development planning which, in context of sustainable development, will have to incorporate social and economic and natural environment requirements. Both the management and the planning are closely related in functional terms and complementary. Moreover, the environmental assessment will contribute to the improvement of the planning assessment by integrating the output into development planning and the development control decisions. All this requires a systematic approach to deal with some regional problems of development and of environmental protection. But potential conflicts between the objectives of management and planning or between development and environment principles, can occur.
Keywords: 330